Port-au-Prince, ville du risque ? Un mythe au prisme d’une urbanisation vulnérable - Johan Milian; Bezunesh Tamru (Études Caribéennes)
This article examines the image of Port-au-Prince as a city deeply marked by natural hazard, an image which has long been attached to the Haitian capital. This characterization needs to be reconsidered. Does Port–au-Prince’s geographic location alone necessitate specific land use planning, costly for a country considered the most impoverished of the Americas? Or, did the disastrous 2010 earthquake, and its aftermath, give rise to this image of a city of risk? Did natural hazard, in a broad sense, become a pretext to accept the existing lack of urban land management policies, especially in evolving peripheries of Port-au-Prince? To explore these questions, we look at two phenomena in the Haitian capital: urban sprawl at the fringes of the city; and settlements located in canyon valleys inside the urban area. We begin with recognition of the historical lack of urban planning in the development of Port-au-Prince. Based on results from two field surveys conducted in 2015 and 2016 (using qualitative semi-structured interviews with a large panel of inhabitants) and a diachronic spatial analysis of land use, we then show the contemporary urban forms that have taken shape through this development; its dynamics; and the acceleration of development reinforced by the 2010 earthquake. Finally, we highlight what appears to be an intellectual construct: that Port-au-Prince is an inherent “risky territory,” whose scattered development planning, overseen by international assistance and private stakeholders, has led to an even more vulnerable urbanization. Regarding the devastating consequences of natural disasters, we show that what differentiates Caribbean cities, with respect to the inherent natural risk attached to their geographic location, is the existence, or lack thereof, of adequate planning policies and capacity for action.